The effects of tour operator’s service quality on travel agents’s customer value, satisfaction and loyalty in Vietnam - Truong, Quoc Dung; Tran, Thi Nguyet Tu (Journal of Finance - Marketing Research, 2023)
Service quality is the most important factor of tour operators determining the relationship between travel agents and tour operators. The authors surveyed 288 travel agents in Vietnam and used Smart-PLS software to test the research hypotheses: Tour operator’s service quality positively impacts travel agent’s customer value, satisfaction, and loyalty; Tour operator’s service quality impacts travel agent’s loyalty through customer value, satisfaction; Customer value impacts travel agent’s loyalty through satisfaction. The result confirmed these relationships in the travel industry B2B environment, satisfaction includes process satisfaction and outcome satisfaction, loyalty includes behavioral loyalty and attitudinal loyalty. Research results help tour operators in Vietnam achieve business efficiency through travel agents to increase satisfaction and maintain travel agents’s loyalty to tour operators, including: (1) providing stable service quality; (2) providing service quality as commitment; (3) providing service as the end consumer’s expectation; (4) always improve service quality; (5) provide competitive products.